FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DI DESA MUNGO KECAMATAN LUAK KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Yosi Ardiana; Rahmanelli Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to find information and find out about (1) the factors that cause children to drop out of school in Mungo Village, Luak District, Lima Puluh Kota Regency, West Sumatra Province. (2) The impact of dropping out of school on the lives of school dropouts. (3) Efforts to deal with the occurrence of children dropping out of school in Mungo Village. The type of research used in this research is descriptive type with a quantitative approach. The population in this study amounted to 55 school dropouts who were in Mungo Village. The sampling technique is the total sampling technique by taking the entire population for the sample. The data collection technique uses the questionnaire filling method. Then for the data analysis technique using the percentage descriptive formula. The results of this study indicate that (1) the factors causing children dropping out of school in Mungo Village are the lack of interest in learning (51%), economic limitations (20%), family environmental factors or broken home (4%), environmental factors. social factors (11%), school environmental factors (9%), health (3%), and young marriage factors (2%). Meanwhile, the most dominant factor is the lack of interest in children's learning. (2) The impact of dropping out of school on the child's life has positive impacts and there are negative impacts. (3) Efforts to overcome this are by establishing package schools, providing assistance and socializing.